Effects of Emotional Freedom Techniques on Compassion, Self-Compassion, and Resilience Among Nursing Students. - Walker, Mark; Horning, Melanie A.; Wright, Lyndsay; Crusse, Elizabeth; Park, Hyunjeong (International Journal for Human Caring, 2026)
This study aimed to enhance self-compassion, compassion for others, and resilience in prelicensure nursing students using Emotional Freedom Techniques (EFT). A pre- and postsurvey design assessed the effectiveness of three EFT sessions on 202 students from two Bachelor of Science programs, revealing comparable demographic profiles between intervention and control groups. Data were collected using the Self-Compassion Scale—Short Form, Compassion Scale, and Connor–Davidson Resilience Scale. Results showed statistically significant increases in resilience, compassion, and self-compassion (p <.05) in the intervention group compared with the control. EFT shows promise as a coping strategy to improve these factors, potentially reducing burnout, turnover rates, and enhancing job satisfaction and patient care in nursing.